Implementasi Kurikulum di Madrasah Tsanawiyah Salafiyah Pondok Pesantren Tremas Pacitan - M. Suyudi; Fitri Hidayati (LP. Ma'arif Janggan Magetan, 2021)
Abstract: This study explains that implementing the curriculum implementation at Madrasah Tsanawiyah Salafiyah Pondok Tremas Pacitan when dismissed, is a qualitative case study- collecting data through interviews, observation, and documentation. According to Huberman, there are three data analysis kinds: data reduction and data presentation, and conclusion drawing. The study results found that: (1) The curriculum at MTs Salafiyah Pondok Tremas Pacitan is a combination of the curriculum from the Ministry of Religion (K 13). Drying Ministry of Religion Using K-13 Drying. (2) The learning time has decreased; two lessons become 1 lesson hour. In the 3rd island class, an additional preparation hour for the final national exam is needed to improve the available material. (3) Implications of cured at MTs Salafiyah Pondok Tremas Pacitan, namely supporting the development of religious scholarship that is not behind in general science. Abstrak: Penelitian ini bermaksud menjelaskan implementasi kurikulum di Madrasah Tsanawiyah Salafiyah Pondok Tremas Pacitan dengan pendekatan adalah kualitatif denganjenis studi kasus. Pengumpulan data melalui wawancara, observasi dan dokumentasi. Analisis data menurut Miles dan Huberman terdapat tiga macam cara yaitu reduksi data, penyajian data, dan penarikan kesimpulan.. Hasil penelitian menemukan bahwa: (1) Kurikulum di MTs Salafiyah Pondok Tremas Pacitan adalah gabungan kurikulum Kementerian Agama (K 13) dan kurikulum pesantren. Kurikulum Kementerian Agama menggunakan kurikulum K-13. (2) Waktu belajar secara umum mengalami pengurangan jam pelajaran, 2 pelajaran menjadi 1 jam pelajaran. Untuk meningkatkan pemahaman materi umum, pada kelas 3 ada tambahan jam persiapan untuk ujian akhir dan nasional. (3) Implikasi kurikulum di MTs Salafiyah Pondok Tremas Pacitan yaitu mendukung pengembangan keilmuan agama tetapi tidak ketinggalan dalam ilmu umum. DOI: https://doi.org/10.33399/edukasia.v2i1.37